2019
DOI: 10.1021/acs.langmuir.9b01240
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for ATP Interaction with Phosphatidylcholine Bilayers

Abstract: ATP is a fundamental intracellular molecule and is thought to diffuse freely throughout the cytosol. Evidence obtained from nucleoside-sensing sarcolemmal ion channels and red blood cells, however, suggest that ATP is compartmentalised or buffered, especially beneath the sarcolemma, but no definitive mechanism for restricted diffusion or potential buffering system has been postulated. In this study, we provide evidence from alterations to membrane dipole potential, membrane conductance, changes in enthalpy of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 58 publications
0
9
0
Order By: Relevance
“…Tryptophan [376][377][378], Glycine [139,284], Glutamate [139], Aginine [379], Alanine [379], 5-aminolevulinic acid and its esters [380], L-dopa [138,199,381,382] Nucleotides ATP [383], UMP [384], DNA [385], ADOMET [381] Sugars and carbohydrates Trehalose [386], Gastrodin [387], Mannitol [199], 1,3,7-trimethyluric acid [388] Neurotransmitters Dopamine [138,[389][390][391][392][393][394][395][396][397], Serotonin [138,378,389,396,[398][399][400][401][402], Adenosine [138], Melatonin [138,229,378,389,[403][404]…”
Section: Antioxidantsmentioning
confidence: 99%
“…Tryptophan [376][377][378], Glycine [139,284], Glutamate [139], Aginine [379], Alanine [379], 5-aminolevulinic acid and its esters [380], L-dopa [138,199,381,382] Nucleotides ATP [383], UMP [384], DNA [385], ADOMET [381] Sugars and carbohydrates Trehalose [386], Gastrodin [387], Mannitol [199], 1,3,7-trimethyluric acid [388] Neurotransmitters Dopamine [138,[389][390][391][392][393][394][395][396][397], Serotonin [138,378,389,396,[398][399][400][401][402], Adenosine [138], Melatonin [138,229,378,389,[403][404]…”
Section: Antioxidantsmentioning
confidence: 99%
“…Evidence suggests that a relationship exists between statin lipophilicity and pleiotropy, which supports the hypothesis that the effects of statins are dependent on where it resides within biological membranes [28][29][30]. It is known that the inclusion of amphiphiles into lipid bilayers impacts lipid bilayer parameters like permeability and thickness [104,105]. Moreover, amphiphilic drugs are soluble in aqueous biological fluids and can diffuse through the body, and partition into membranes [106,107].…”
Section: Statin-membrane Interactionsmentioning
confidence: 56%
“…This could be explained by K + bridging between PEO and the phosphate group of dUTP since it was shown that ATP associates with DOPC bilayers. [ 49 ] These membrane interactions led to heterogeneous distribution of FITC‐12‐d‐UTP (Figure 6D and Figures S34 and S35, Supporting Information) and often resulted in tight contacts between the GUVs and formation of tissue‐like structure (Figure S36, Supporting Information).…”
Section: Resultsmentioning
confidence: 99%